An integrated process for enzymatic catalysis allowing product recovery and enzyme reuse by applying thermoreversible aqueous biphasic systems. Issue 6 (28th February 2018) - Ferreira, Ana M.; Passos, Helena; Okafuji, Akiyoshi; Tavares, Ana P. M.; Ohno, Hiroyuki; Freire, Mara G.; Coutinho, João A. P.
Abstract : An integrated biocatalysis-separation process: the reaction step occurs in a homogeneous medium, followed by enzyme and product separation in a liquid–liquid system promoted by temperature changes. Abstract : Herein, thermoreversible aqueous biphasic systems (ABS) composed of ammonium-based zwitterions (ZIs) and polymers are disclosed to act as integrated bioreaction–separation processes. The biocatalytic reaction involving laccase occurs in homogeneous media, after which small changes in temperature induce the formation of two phases and the complete separation of the enzyme from the products in a single-step. These systems also allow the recovery and reuse of the enzyme, along with the ZI-rich phase, contributing towards the development of sustainable biocatalytic processes.